2020
DOI: 10.1371/journal.pone.0229171
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, expression, and in situ hybridization analysis of MnGPx-3 and MnGPx-4 from oriental river prawn, Macrobrachium nipponense, in response to hypoxia and reoxygenation

Abstract: Glutathione peroxidase (GPx) has been the focus of increased research because of its important role as an antioxidant and in reactive oxygen species (ROS) induced damage repair. Studies on GPxs have relevance with Macrobrachium nipponense because it has poor tolerance to hypoxia in Macrobrachium nipponense. The two subunits named as MnGPx-3 and MnGPx-4 according to the glutathione peroxidase nomenclature system. Both full-length cDNAs were cloned from the hepatopancreas. In this study, we analyzed the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Currently, SNP studies in aquatic animals have predominantly focused on growth traits; previous studies successfully identified growth-related SNP loci in several shrimp species, including M. japonicus [ 33 ], M. rosenbergii [ 34 ], and Litopenaeus vannamei [ 35 ]. Previous studies also reported that lactate dehydrogenase [ 36 ], glutathione peroxidase [ 37 ], p53 [ 38 ], GST [ 9 ], and caspase-3 [ 39 ] were involved in hypoxia tolerance in M. nipponense . GST-2 is an important detoxification enzyme, with key roles in responses to hypoxia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, SNP studies in aquatic animals have predominantly focused on growth traits; previous studies successfully identified growth-related SNP loci in several shrimp species, including M. japonicus [ 33 ], M. rosenbergii [ 34 ], and Litopenaeus vannamei [ 35 ]. Previous studies also reported that lactate dehydrogenase [ 36 ], glutathione peroxidase [ 37 ], p53 [ 38 ], GST [ 9 ], and caspase-3 [ 39 ] were involved in hypoxia tolerance in M. nipponense . GST-2 is an important detoxification enzyme, with key roles in responses to hypoxia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the discovery of hypoxia-related genes in aquatic animals entered a new stage, and a lot of hypoxia-related genes in mammals were cloned homologously into aquatic animals. At this stage, some important hypoxia-related genes were identified, including a series of well-known antioxidant genes [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%